Nickel Acetate-Assisted Graphitization of Porous Activated Carbon at Low Temperature for Supercapacitors With High Performances - Zhang, Xiaohui; Qiu, Zhian; Li, Qingyu; Liang, Libo; Yang, Xiaofei; Lu, Shaorong; Xiang, Dinghan; Lai, Feiyan (Frontiers in Chemistry, 2022)
Catalytic graphitization opens a route to prepare graphitic carbon under fairly mild conditions. Biomass has been identified as a potentially attractive precursor for graphitic carbon materials. In this work, corn starch was used as carbon source to prepare hollow graphitic carbon microspheres by pyrolysis after mixing impregnation with nitrate salts, and the surface of these carbon microspheres is covered with controllable pores structure. Under optimal synthesis conditions, the prepared carbon microspheres show a uniform pore size distribution and high degree of graphitization. When tested as electrode materials for supercapacitor with organic electrolyte, the electrode exhibited a superior specific capacitance of 144.8 F g-1 at a current density of 0.1 A g-1, as well as large power density and a capacitance retention rate of 93.5% after 1000 cycles in galvanostatic charge/discharge test at 1.0 A g-1. The synthesis extends use of the renewable nature resources and sheds light on developing new routes to design graphitic carbon microspheres.